Hero at the fall : a Rebel of the sands novel - Hamilton, Alwyn (Viking, 2017)
"When gunslinging Amani Al'Hiza escaped her dead-end town, she never imagined she'd join a revolution, let alone lead one. But after the bloodthirsty Sultan of Miraji imprisoned the Rebel Prince Ahmed in the mythical city of Eremot, she doesn't have a choice. Armed with only her revolver, her wits, and her untameable Demdji powers, Amani must rally her skeleton crew of rebels for a rescue mission through the unforgiving desert to a place that, according to maps, doesn't exist. As she watches those she loves most lay their lives on the line against ghouls and enemy soldiers, Amani questions whether she can be the leader they need or if she is leading them all to their deaths"--Amazon.com.